Exploration of Students' Mathematical Communication Abilities - Na'im, Zahrin Nurun; Mukhlis, Mohammad (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2024)
It is of great importance for students to develop their mathematical communication skills. Mathematical communication skills play a pivotal role in mathematics education. Mathematical communication enables students to share ideas, clarify their understanding, and express their knowledge. The acquisition of proficient mathematical communication skills will facilitate a more profound comprehension of mathematical concepts. The objective of this study is to describe students' mathematical communication skills regarding flat-sided cubes and cuboids, with a focus on three indicators of mathematical communication skills as outlined by the National Council of Teachers of Mathematics (NCTM). The research design employed is that of descriptive research with a qualitative approach. The findings indicated that students exhibited a diverse range of mathematical communication skills. The students were divided into three categories according to their mathematical abilities. A more detailed examination of each category can be found in this article.